Tourists' knowledge on the status of UNESCO world heritage site for Gunung Mulu National Park - Ibrahim, Mohamad Syahrul Nizam; Adam Assim, Mohamad Ibrani Shahrimin; Johari, Shazali; Wan Mohammad, Syarifah Kamariah; Hassan, Suziana (Malaysian Forester, 2023)
Gunung Mulu National Park (GMNP) has gained recognition as one of the UNESCO World Heritage Sites (WHS) in Sarawak due to its outstanding universal value for natural heritage. This status is particularly significant in supporting the in-situ biodiversity conservation efforts in high-endemic areas of GMNP. Being a WHS site has attracted many tourists to that park. However, the information about visitors’ knowledge of the status awarded to GMNP is still limited. Thus, this study aims to examine the knowledge of tourists on the WHS status in GMNP. Online open-ended questionnaire was distributed to 85 individuals using social media platforms. The data on their knowledge of WHS status was categorised using thematic analysis and transferred into SPSS for descriptive analysis. Respondents' knowledge on the status of the park has been classified into eight themes, namely protection and conservation of natural heritage; tourist attractions; holistic national park management; preserve outstanding value; funds for restoration, preservation, and training; promote national and local pride; provide massive international attention towards biodiversity conservation; and community well-being. The respondents are considered to be knowledgeable of the status and importance of WHS status based on the knowledge they possess from their experiences visiting GMNP. It portrays a positive indication that visitors gain knowledge from their visit and participation in the activities at GMNP, parallel to UNESCO’s initiative towards promoting biodiversity conservation and sustainability of the park.